CO2 spectroscopy and forward/inverse radiative transfer modelling in the thermal band using IASI spectra. (January 2019) - Serio, C.; Masiello, G.; Camy-Peyret, C.; Liuzzi, G.
Highlights: CO2 spectroscopy and forward modelling accuracy for the ν 2 and ν 3 absorption bands. CO2 retrieval performance using the whole IASI spectral coverage, 645–2760 cm − 1 . Four years long record of IASI retrievals and comparison with in situ observations. IASI data and products available on request. Abstract: Spectroscopy and forward modelling consistency and accuracy in the ν 2 and ν 3 fundamental absorption bands of CO2 have been assessed through IASI (Infrared Atmospheric Sounder Interferometer) spectra recorded over the Pacific Ocean Manus island (Papua New Guinea) validation station. Until 2014, the Manus station has been operated within the Global Climate Observing System (GCOS) Reference Upper-Air Network (GRUAN) and has provided high quality radiosonde observations for temperature and water vapour. Because of its longitude and close to Equator position, the radiosonde regular launches at 00:00 and 12:00 UTC naturally coincide with Metop/IASI overpasses. Thus, IASI soundings and radiosonde observations can be co-located within a time slot of 30 min and a spatial distance of less than 50 km. Considering that radiosonde observations are limited to the troposphere and lower stratosphere, the usual analysis of spectral residuals (Observations-Calculations) yields the possibility to directly validate the spectroscopy of CO2 channels, which are sensitive to the troposphere. Furthermore, the combined use of radiosonde and ECMWF (European Centre for Medium range Weather Forecasts) analysis, to extend the radiosonde profiles in the upper atmosphere, has allowed us to check the CO2 spectroscopic consistency in spectral channels that are sensitive to the stratosphere. Our analysis shows that state-of-art CO2 spectroscopy and forward modelling have errors that are comparable or better than the IASI radiometric noise. This level of accuracy has proved to be enough for providing good CO2 retrievals. The fidelity of CO2 retrieval has been assessed by using in situ observations from the HIAPER (High-performance Instrument Airborne Platform for Environmental Research) Pole-to-Pole Observations (HIPPO) flights and the Mauna Loa (Hawaii) validation station. An analysis of a four-year record of IASI soundings (2014–2017) over Mauna Loa shows that the correlation between IASI retrieved CO2 column amounts and in situ observations is ≈ 0.95. The IASI derived CO2 also shows trend and seasonality, which are consistent with those derived from in situ observations. The retrieval analysis has also been extended to N2 O, which plays an important role in assessing the consistency of the forward model in the N2 O/CO2 ν 3 band. We have found that N2 O estimated from IASI radiances is accurate enough to derive a satellite growth rate consistent with in situ observations of less than 1 ppbv per year (but with some interannual variations).